(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The pro-globalisers arenot correct in their claims that integration with the world market has workedwonders in reducing poomes in China and India. The critics who claim thatglobalisation has contributed to a widening of dissimilarity are also off themark. A close examination of the data suggests that a more nuancedunderstanding is called for.